Tocilizumab combination therapy or monotherapy or methotrexate monotherapy in methotrexate-naive patients with early rheumatoid arthritis: 2-year clinical and radiographic results from the randomised, placebo-controlled FUNCTION trial. Issue 7 (7th April 2017) - Burmester, Gerd R; Rigby, William F; van Vollenhoven, Ronald F; Kay, Jonathan; Rubbert-Roth, Andrea; Blanco, Ricardo; Kadva, Alysha; Dimonaco, Sophie
Abstract : Objective: Investigate whether the efficacy and safety of intravenous tocilizumab (TCZ) demonstrated at week 52 in patients with early rheumatoid arthritis (RA) are maintained to week 104. Methods: Methotrexate (MTX)-naive patients with early progressive RA were randomly assigned to double-blind 4 mg/kg TCZ+MTX, 8 mg/kg TCZ+MTX, 8 mg/kg TCZ+placebo or placebo+MTX for 104 weeks. Patients not receiving 8 mg/kg TCZ and not achieving Disease Activity Score-28 joints (DAS28-erythrocyte sedimentation rate (ESR)) ≤3.2 at week 52 switched to escape therapy (8 mg/kg TCZ+MTX). Analyses were exploratory. Results: Intent-to-treat and safety populations included 1157 and 1153 patients, respectively. DAS28-ESR remission (<2.6) rates were maintained from weeks 52 to 104 (eg, 8 mg/kg TCZ+MTX, 49.3% to 47.6%). Placebo+MTX and 4 mg/kg TCZ+MTX escape patients' week 104 response rates were 51.4% and 30.5%, respectively. Inhibition of radiographic progression was maintained with 8 mg/kg TCZ (eg, 8 mg/kg TCZ+MTX mean (SD) change from baseline in modified total Sharp score: 0.13 (1.28), week 52; 0.19 (2.08), week 104). The safety profile of TCZ was consistent with that of previous reports. Conclusions: Patients with early RA treated with TCZ monotherapy or TCZ+MTX maintained clinical benefits during their second year of treatment with no new safety signals. Trial registration number: NCT01007435; Results.